SISTEM ASPEK DALAM BAHASA TORAJA - Jusmianti Garing (SAWERIGADING, 2013)
This study is aimed to investigate the aspect systems of Torajan language. The study used qualitative method byanalyzing Torajan discourses. It describes the aspect systems of Torajan language. The results show that thereare two main aspects of Toraja, a perfective and an imperfective aspect. The perfective aspect is marked with thesuffix -mi, -mo, and negation taeq, whereas the imperfective aspect conveys progressive and iterative meaning.Those features are distinguished by affixes. Prefixes me(N)-, sipaq-, si-, to-, maq-, and sufixes -kanni, -pa conveythe imperfective-progressive meaning which indicates that the action is still ongoing. Whereas, the prefix maqthatmerges in reduplication verbs convey the iterative meaning. AbstrakPenelitian ini bertujuan menginvestigasi sistem aspek dalam bahasa Toraja. Penelitian ini menggunakan metodekualitatif dengan objek kajian wacana yang berbahasa Toraja. Wacana tersebut menggambarkan sistem aspekdalam bahasa Toraja. Hasil penelitian menunjukkan bahwa ada dua sistem aspek dalan bahasa Toraja yakniaspek perfektif dan imperfektif. Aspek perfektif ditandai dengan penggunaan klitik -mi, -mo, dan negasi taeq.Selanjutnya, aspek imperfektif menyatakan makna progresif dan iteratif. Makna-makna tersebut diindikasikanmelalui proses afiksasi. Prefiks me(N)-, sipaq-, si-, to-,maq-, dan sufiks -kanni,-pamenyatakan makna imperfektifprogresif yang mengindikasikan kejadian yang masih berlangsung, sedangkan prefiks maq- yang bergabungpada kata kerja ulangan menyatakan makna iteratif.